FUNCTIONALIZATION OF THE ROLE OF ACADEMIC ADVISORS IN STUDENT STUDIES AT THE TARBIYAH AND TEACHER TRAINING FACULTY OF UIN SULTAN MAULANA HASANUDDIN - Ngaisah, Siti; Utami, Vina Dwi; Audina, Mia; Helnanelis, Helnanelis (Indonesian Journal of Educational Development (IJED), 2024)
Academic guidance is one of the success factors for students in completing their studies well and on time. The aim of this research is to find out what problems are faced by the Tarbiyah and Teacher Training Faculty of UIN Sultan Maulana Hasanuddin Banten regarding academic supervision, as well as to synthesize solutions to reinstate the role of academic supervisors. This research uses qualitative research methods, field research. The data collection methods used are interview and documentation methods. Data analysis uses the Miles and Huberman analysis model. The results of the research show that the problems faced by Tarbiyah and Teacher Training Faculty UIN Sultan Maulana Hasanuddin Banten are students who are less active, lack of communication between academic supervisors and students, lecturers who are difficult to find, not yet well programmed, lack of student initiative in raising problems and lecturer initiative in asking about developments. student. The solution offered in this research is to create and update academic guidance, socialization and digital platform guides.